CONSTITUTIONAL PROTECTION OF THE ENVIRONMENT: EVOLUTION IN EUROPE BETWEEN ANTHROPOCENTRISM AND ECOCENTRISM - THE ITALIAN CASE - Porena, Daniele (Revista Eletrônica Direito e Política, 2014)
ABSTRACT In modern European constitutions the concept of the environment has been considered in two main models: placing the environment and its protection within jurisdiction for the individual under the form of the right to a healthy environment or placing it within the framework of collective, widespread responsibility, such as generally obliging individuals and public authorities to protect the environment. In the Italian Constitution, no article identified the value of the environment and obliged protection. Protection of the environment was ensured only through the Constitutional Court’s interpretations of combinations of articles 2, 9 and 32, which laboriously worked to define the terms of constitutional protection of environment. Over time case law and legal opinion came to consolidate that the environment in the Italian legal system is a fundamental constitutional concept.